Tapeworm chromosomes: their value in systematics with instructions for cytogenetic study - Orosova, Martina; Spakulova, Marta (Folia parasitologica, 2018)
The history and value of cytogenetic features for addressing questions of the evolution and systematics of tapeworms (Cestoda) are briefly reviewed along with instructions for collecting karyological data. As a supplement to worm morphology, chromosome number and morphology have been helpful in determining the systematic status of some genera in the Diphyllobothriidae and species in the Bothriocephallidea. In addition, many new techniques for chromosome analysis have been recently applied in morphological and molecular studies of invertebrates, including tapeworms. Methods of molecular karyology, fluorescence in situ hybridisation, and chromosomal location of satellite DNA, microsatellites or histone genes may also provide useful data to inference of taxonomic relationships and for revealing trends or general lines of chromosome evolution. However, as karyological data are available only for few tapeworms, they are seldom an integral part of evolutionary and taxonomic studies of cestodes. A primary reason for this lack of karyological data may lie in general difficulties in working with tapeworm chromosomes. To address these problems, herein we present a well-tested, step-by-step illustrated guide on the fixation of tapeworm material and preparation of their chromosomes for cytogenetic studies. The technique requires standard glassware, few reagents and simple equipment such as needles; it can also be used on other neodermatan flatworms.
Keywords: cytogenetika; chromozomy; Chromosomes; Cytogenetics; karyotype; Animals; zvířata; Parasitology; methodological manual; cytogenetics; parazitologie; Cestoda